2015
DOI: 10.1136/postgradmedj-2015-133648
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in intravenous drug users: a review article

Abstract: Approximately 10% of infective endocarditis (IE) involves the right side of the heart with the majority of these cases occurring in intravenous drug users. Patients are less likely to present with classical IE signs of a new murmur and peripheral stigmata, are more frequently immunocompromised and often have significant social difficulties. These factors result in both diagnostic and therapeutic challenges in this patient group that are not often seen in other patient populations with IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 27 publications
4
47
0
Order By: Relevance
“…To our knowledge, this is the largest study (n=33) showcasing detailed survey data regarding injection practices of PWID with IE. Previous studies suggested that IE in PWID was more frequently seen in males, younger patients and those with concurrent HIV infections (3,8,9). Our results show similar age distribution of IE, with it occurring in younger individuals (mean age 34).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…To our knowledge, this is the largest study (n=33) showcasing detailed survey data regarding injection practices of PWID with IE. Previous studies suggested that IE in PWID was more frequently seen in males, younger patients and those with concurrent HIV infections (3,8,9). Our results show similar age distribution of IE, with it occurring in younger individuals (mean age 34).…”
Section: Discussionsupporting
confidence: 84%
“…This infectious complication of intravenous drug use (IVDU) is associated with significant morbidity and mortality requiring extensive and costly(1,2) multidisciplinary care (7). PWID are at risk of IE due to: comorbidities of HIV, hepatitis C and skin and soft tissue infections; non-sterile injection practices; and the reuse of injection drug preparation equipment (IDPE) (2,4,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Deep tissue infections (DIT) are pathogenic infections involving subcutaneous tissues that may proliferate to surrounding tissues and muscles [1]. This is particularly due to the introduction of bacteria into the venous circulation or subcutaneous tissue, which is common among those who inject drugs [2,3]. Multiple studies have indicated increasing rates of infective endocarditis [4][5][6][7], osteomyelitis [3,[8][9][10][11][12][13][14][15], and septic arthritis associated with intravenous drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Infective Endocarditis (IE) is one of the most severe complications in intravenous drug abusers. The tricuspid valve is the most frequently affected [1]. Staphylococcus aureus is the most common etiologic agent [2].…”
Section: Introductionmentioning
confidence: 99%